2021
DOI: 10.1111/pin.13091
|View full text |Cite
|
Sign up to set email alerts
|

Histological alterations following fine‐needle aspiration for parathyroid adenoma: Incidence and diagnostic problems

Abstract: This study aimed to clarify the histological alterations following fine‐needle aspiration for parathyroid adenoma and discuss the occurrence of diagnostic problems. Among the 392 patients with parathyroid adenoma who underwent resection, fine‐needle aspiration was performed for 21 (5.1%) parathyroid adenoma nodules. Histological findings that were significantly more frequent in cases that underwent fine‐needle aspiration were considered histological alterations following fine‐needle aspiration for parathyroid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…41 Potential complications of FNA includes hematoma, parathyroid abscess, disruption of the lesion and seeding along the needle tract (parathyromatosis) or dense fibrotic reaction to the needle. [57][58][59][60][61] These uncommon events may rarely convert a minimally invasive surgery to a standard surgical approach. 62 In the majority of reported series of parathyroid FNA no severe complication occurred and in the present study, there were no reported complications associated with FNA of parathyroid gland.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Potential complications of FNA includes hematoma, parathyroid abscess, disruption of the lesion and seeding along the needle tract (parathyromatosis) or dense fibrotic reaction to the needle. [57][58][59][60][61] These uncommon events may rarely convert a minimally invasive surgery to a standard surgical approach. 62 In the majority of reported series of parathyroid FNA no severe complication occurred and in the present study, there were no reported complications associated with FNA of parathyroid gland.…”
Section: Discussionmentioning
confidence: 99%
“…Potential complications of FNA includes hematoma, parathyroid abscess, disruption of the lesion and seeding along the needle tract (parathyromatosis) or dense fibrotic reaction to the needle 57–61 . These uncommon events may rarely convert a minimally invasive surgery to a standard surgical approach 62 .…”
Section: Discussionmentioning
confidence: 99%
“…While these features should raise the suspicion of malignancy, these histologic features alone are not diagnostic as they can be seen in both PA and parathyroid hyperplasia making the diagnosis of PC challenging 6,11,40,41. In particular, fibrosis can be seen post–fine-needle aspiration (FNA), after therapeutic ethanol injection, in the setting of secondary/tertiary HPT, and in large, degenerated adenomas 42–44. When areas of fibrosis are identified, a careful search for prior manipulations such as FNA should be performed.…”
Section: Pathology Of Hyperparathyroidismmentioning
confidence: 99%
“…6,11,40,41 In particular, fibrosis can be seen post-fine-needle aspiration (FNA), after therapeutic ethanol injection, in the setting of secondary/tertiary HPT, and in large, degenerated adenomas. [42][43][44] When areas of fibrosis are identified, a careful search for prior manipulations such as FNA should be performed. Knowledge of the history of chronic renal failure and secondary or tertiary HPT is also useful.…”
Section: Parathyroid Carcinomamentioning
confidence: 99%